2007
DOI: 10.1002/cncr.22600
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year survival after surgical treatment for kidney cancer

Abstract: BACKGROUND.Kidney cancer's rising incidence is largely attributable to the increased detection of small renal masses. Although surgery rates have paralleled this incidence trend, mortality continues to rise, calling into question the necessity of surgery for all patients with renal masses. Using a population‐based cohort, a competing risk analysis was performed to estimate patient survival after surgery for kidney cancer, as a function of patient age and tumor size at diagnosis.METHODS.With data from the Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
139
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(148 citation statements)
references
References 34 publications
2
139
1
6
Order By: Relevance
“…Additionally, only one study authored by Komai et al [14], recorded a survival advantage in young patients with T1-T2 RCC stages relative to the older counterparts. Second, Aziz et al [16] relied on the CORONA database, also showed that young patients (<40 yrs) had lower CSM compared to the older counterparts within a cohort of patients with stage T1-4, N0-1, M0-1. Finally, Rampersaud et al [15] confirmed the less aggressive natural history of RCC for patients age<59 yrs relative to those aged ≥60 yrs across all localized and non-localized stages (T1-4, N0-1, M0-1).…”
Section: Cuaj -Original Research Bandini Et Al Effect Of Age On Cancementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, only one study authored by Komai et al [14], recorded a survival advantage in young patients with T1-T2 RCC stages relative to the older counterparts. Second, Aziz et al [16] relied on the CORONA database, also showed that young patients (<40 yrs) had lower CSM compared to the older counterparts within a cohort of patients with stage T1-4, N0-1, M0-1. Finally, Rampersaud et al [15] confirmed the less aggressive natural history of RCC for patients age<59 yrs relative to those aged ≥60 yrs across all localized and non-localized stages (T1-4, N0-1, M0-1).…”
Section: Cuaj -Original Research Bandini Et Al Effect Of Age On Cancementioning
confidence: 99%
“…It should also be noted that 3 single institution studies failed to show a statistically significant relationship between age and CSM in patients with RCC. Specifically, Hollingsworth et al [16] reported a lack of statistically significant difference between young and old individuals in regard to CSM considering stages T1-2, N0, M0 RCC. While, Thompson et al [17] and Gillett et al [18] did not observe a significant CSM disadvantage for individuals with older age considering localized (T1-4, N0, M0) and non-localized (any T, N1 or M1) RCC.…”
Section: Cuaj -Original Research Bandini Et Al Effect Of Age On Cancementioning
confidence: 99%
“…Up to one third of patients older than 70 years who are treated for kidney tumors have been found to die of other causes. 5 Such ''treatment disconnect'' may be due to the potential of surgical treatment by radical nephrectomy (RN) increasing postoperative CKD morbidity, which in turn increases associated competing causes of death.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the disease represents approximately 2.0% of all new cases of cancer and over 100.000 deaths worldwide (3). Improvements in imaging diagnosis may have contributed to the rising incidence of RCC over the past three decades, since this rise in incidence is mainly a result of the increasing detection of small tumors (4). However, at least in the United States, both incidence of late-stage RCC and mortality rates due to the disease have also been rising, implying that improvements in the ability to diagnose RCC are being outweighed by the increasing prevalence of some of the risk factors for this tumor (5).…”
Section: Introductionmentioning
confidence: 99%